Analisis Penilaian Tingkat Kesehatan Bank Dengan Metode Camel Studi Kasus Pada PD BPR-BKK Boyolali Cabang Andong Periode Tahun 2012-2014 - Kusuma, Ernanda Indra; , Drs. Fauzan, SE, Ak, M.Si (2016)
This research was aimed to identify mount the health of PD BPR BKK Boyolali Andong Branch pursuant to which have been specified by Indonesia Bank (BI) with the Invitor - Invite the Banking going into effect evaluated from capital, quality of productive asset, management, rentability and liquidity. The data technique analysis in this research was using CAMEL method to identify mount the health of PD BPR BKK Boyolali Andong Branch. Pursuant to standard mount the health at aspect capital/capital measured with the capital ratio (CAR), CAR ratio PD BPR BKK Boyolali Andong Branch cannot be presented because branch office only representing part of head office, so that capital enumeration only can be calculated in Head Office of PD BPR BKK Boyolali, representing aliance from 17 Branch Office and 1 Head Office Operational. At asset quality / Quality of Productive Asset aspect measured with the ratio, KAP ratio 2012, 2013 and 2014 including criterion between 0,00 - 10,35%, so that mount the health for the quality productive asset factor of HEALTHY categorized. Pursuant to standard mount the health measured from final credit value, assess the final credit show 2012, 2013 and 2014 showing number where staying in between 20,50 - 25,00, so that mount the health for the productive asset quality factor of HEALTHY categorized. Pursuant to standard mount the health measured from final credit value, assess the final credit shows 2012, 2013 and 2014 showing number where staying in between 20,50 - 25,00, so that mount the health for the productive asset quality factor of HEALTHY categorized. At aspect management can be only measured in Head Office, because Andong Branch Office only representing the part of 17 Branch Office and 1 Operational Head Office while Top Management in Head Office of PD BPR BKK Boyolali. At aspect of earning ability/rentability measured from final credit value, assess the final credit show 2012, 2013 and 2014 showing each number; 5; 5; and 5 where staying in between 4,05 - 5,00; so that mount the health for the ROA factor HEALTHY categorized. Liquidity Sufficiency specially Cash Ratio measured from final credit value, assess the final credit show 2012, 2013 and 2014 showing number 5 where staying in between 4,05 - 5,00; so that mount the health for the liquidity factor HEALTHY categorized. Keyword: level of bank healthy, capital, quality of productive asset, management, rentability and liquidity.